Głos jako tworzywo postaci operowej. Historyczny zarys wokalnej typologii głosów - Kicińska, Hanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
This study presents the historical range of topics related to the typology of singing voices and how they are linked to the character constituting the building material of an operatic character. This six-part overview presents the subsequent stages of the formation of the status and role of particular voices in the theory and practice of musical performance, with particular emphasis on specific vocal phenomena key to the development of operatic and solo singing: the so-called covering, haute-contre, bass-baritone and boy soprano. The reason behind the diachronic presentation of the vocal terms is to order and systematise the transformations that vocal practice, musical nomenclature and musical performance have undergone over the centuries.